Uso de bloques lógicos para la formación de conjuntos en estudiantes del nivel primaria - Chiroque Pérez, Marilyn Esther (2021)
This research dealt with the use of logic blocks for the formation of sets in second grade primary school students, as for the logic blocks applied in this proposal, it can be said that they are pieces of wood or plastic with 4 different characteristics: Color (3): Blue, Yellow and Red. Shape (4): Square, Rectangle, Circle and Triangle. Size (2): Large and Small. In relation to the variable formation of sets, with the proposal the child managed to organize sets according to similarities and, we can say that the students managed to establish that a set is made up of elements of the same nature, that is, elements differentiated from each other but possessing In common certain properties or characteristics, and that they can have between them, or with the elements of other sets, certain relationships. Based on what was stated and as a consequence of the subject of study, it can be affirmed that they worked with the competence "Solve quantity problems", specifically the ability "Translate quantities and numerical expressions", where the students managed to develop their mathematical thinking and strategies for problem solving, considering new knowledge about classification and set formation, using logic blocks.